2021
DOI: 10.1177/19484992211020767
|View full text |Cite
|
Sign up to set email alerts
|

Status of Band and Orchestra Programs in North Carolina

Abstract: The purpose of this study was to examine K–12 instrumental music education in North Carolina. Specifically, we investigated course offerings, teacher demographics, teaching responsibilities, and music program funding. We administered a survey to the members of the North Carolina Music Educators Association listserv who indicated band or orchestra as their teaching area. Participants identified themselves as teachers of orchestra ( n = 44), band ( n = 173), or a hybrid of both ( n = 17). Of schools that offered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…For example, several studies have estimated the percentage of music teachers identifying as White to range between 82% and 92%, a higher proportion than the general teacher population (Elpus, 2015a(Elpus, , 2022cGardner, 2010;Matthews & Koner, 2017). As with students, music teacher demographics varied based on state, grade level, and content area (Miller et al, 2021;R. D. Shaw & Auletto, 2022;Smith et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several studies have estimated the percentage of music teachers identifying as White to range between 82% and 92%, a higher proportion than the general teacher population (Elpus, 2015a(Elpus, , 2022cGardner, 2010;Matthews & Koner, 2017). As with students, music teacher demographics varied based on state, grade level, and content area (Miller et al, 2021;R. D. Shaw & Auletto, 2022;Smith et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…D. Shaw & Auletto, 2022; Smith et al, 2018). For example, Miller et al (2021) found disparities in self-reported teacher gender between band and orchestra teachers in North Carolina: Approximately 37% of band or hybrid teachers identified as female, and nearly 59% of orchestra teachers identified as female. In comparison, Smith et al (2018) found that approximately 64% of orchestra teachers across the United States identified as female.…”
Section: Introductionmentioning
confidence: 99%
“…In state-level status studies conducted after 1997, string music education access and enrollment varied significantly among communities (see Table 1). Results from Kansas, North Carolina, and Oregon indicated moderate growth among districts offering orchestra whereas results from Indiana showed a slight decline (Ihas, 2019;Miller et al, 2021;Schmidt et al, 2006;Tast, 2014). Other measures of state-level program status included the percentage of secondary schools offering string classes, the percentage of secondary students that participated in orchestra, and the average orchestra program size among schools offering orchestra (see Table 1).…”
Section: Status Of Strings At the State Levelmentioning
confidence: 99%
“…En estos centros de enseñanza, donde el carácter formativo es muy específico e individualizado, se ha sufrido de una manera muy acuciada el replanteamiento metodológico que se viene exigiendo a los centros escolares durante los meses de confinamiento. A ello se une el profundo proceso de transformación que vienen experimentando estas instituciones en los últimos años (Bennet & Stanberg, 2006;Carey & Grant, 2015;Miller et al, 2021), que han visto cómo el perfil "romántico" de músico virtuoso-solista que defendían sus planes de estudios ha dado paso a una amplia oferta formativa multidisciplinar que trata de dar respuesta y cobertura al gran abanico de salidas profesionales que la sociedad contemporánea exige a la música (Ponce de León y Lago, 2012).…”
Section: Introductionunclassified